2016
DOI: 10.1080/19942060.2016.1245629
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the pressure drop inside a rectangular channel with a built-in U-shaped tube bundle heat exchanger

Abstract: A simplified approach which utilizes an isotropic porous medium model has been widely adopted for modeling the flow through a compact heat exchanger. With respect to situations where the compact heat exchangers are partially installed inside a channel, such as the application of recuperators in an intercooled recuperative engine, the use of an isotropic porous medium model needs to be carefully assessed because the flow passing through the heat exchanger is very complicated. For this purpose, in this study the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In a recent study, Wang et al (2018) found reattachment and co-shedding ow regimes in tandem con guration of rods. Liu et al (2017) measured the pressure drop in a rectangular channel with a built-in double-U-shaped tube bundle with different inclinations and calibrate a numerical model emulating the rod bundle with a porous medium.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, Wang et al (2018) found reattachment and co-shedding ow regimes in tandem con guration of rods. Liu et al (2017) measured the pressure drop in a rectangular channel with a built-in double-U-shaped tube bundle with different inclinations and calibrate a numerical model emulating the rod bundle with a porous medium.…”
Section: Introductionmentioning
confidence: 99%
“…It has been applied to identify the optimized geometry of a pipe heat exchanger used in HVAC applications (Selma et al, 2014), assess the effect of baffle clearances on pressure drop and thermal performance in a shell and tube heat exchanger (Batalha Leoni et al, 2017), investigate trefoil-hole baffles on the enhancement of heat transfer in the shell side of a small size heat exchanger (You et al, 2015), study the effects of distributor design parameters (tube pitch, header diameter, tube diameter, number of tubes and inlet or outlet pipe diameter) on the uniformity of flow rate in manifolds (Gandhi et al, 2012), and verify the optimal structural parameters obtained from orthogonal tests for a heat exchanger (Sun et al, 2019). Liu et al (Liu et al, 2017) simulated the pressure drop and flow field inside a rectangular channel with a built-in U-shaped tube bundle heat exchanger, where the heat exchanger was described as an isotropic porous medium. López del Prá et al (López del Prá et al, 2010) simulated a gas jet issued from a guillotine tube type breach into a tube bundle to investigate the failure stage of shell and tube heat exchangers by using CFD technology.…”
Section: Introductionmentioning
confidence: 99%